A Multilayer Fuzzy Cognitive Maps approach to the cloud adoption decision support problem - Christoforou, Andreas; Andreou, Andreas S. (My University, 2015)
As modern computing relies more and more on distributed solutions of services and resources over the cloud, the need of potential users to assess whether the transition from traditional software systems to the cloud would be to their benefit becomes even greater. Cloud vendors also seek ways to study beforehand the behavior of potential users with respect to their decision to adopt the cloud environment so as to take actions towards enhancing the positive side. Therefore, the study of the parameters forming the environment behind the cloud adoption decision is of paramount importance to both users and vendors. In this context the present paper proposes a multi-layer FCM approach which models a number of factors which play a decisive role to the cloud adoption issue and offers the means to study their influence. The factors are organized in different layers which focus on specific aspects of the cloud environment, something which, on one hand, enables tracking the causes for the decision outcome, and on the other offers the ability to study the dependencies between the leading determinants of the decision. The construction and analysis of the model is based on factors reported in the relevant literature and the utilization of experts' opinion. The efficacy and applicability of the proposed approach are demonstrated through four real-world experimental cases.
Keywords: Cloud adoption; Decision support; Multi-layer fuzzy cognitive maps